The Role of Smartphone Addiction on Bed Procrastination and Mindful Eating Behavior in Adolescents from an Islamic Psychology Perspective - Karimulloh; Syiffa Azahra Tri Rahayu (IJIP : Indonesian Journal of Islamic Psychology, 2024)
The large number of Muslims who excessively use smartphones, even at night when sleeping and while eating, needs to be reviewed from an Islamic psychology perspective. This research aims to look at the role of smartphone addiction on bed procrastination and mindful eating behavior from an Islamic psychology perspective. This research method is library research using the Al-Qur'an, Al-Hadith, relevant books, and journal articles to analyze inductive data and draw comprehensive conclusions. The research results show that Islam teaches its followers not to overdo any behavior, including using smartphones. Smartphone addiction behavior, which results in delayed sleep and also eating without being mindful, includes behavior of being ungrateful for the blessings of Allah SWT. Islam encourages teenagers to imitate the behavior of the Prophet Muhammad, including sleeping and eating, namely by sleeping after performing the Isha prayer and practicing mindful eating while eating.